Renal replacement therapy in patients with acute myocardial infarction: Rate of use, clinical predictors and relationship with in-hospital mortality. (1st March 2017) - Marenzi, Giancarlo; Cosentino, Nicola; Marinetti, Andrea; Leone, Antonio M.; Milazzo, Valentina; Rubino, Mara; De Metrio, Monica; Cabiati, Angelo; Campodonico, Jeness; Moltrasio, Marco; Bertoli, Silvio; Cecere, Milena; et al.
Abstract: Objectives: We evaluated the rate of use, clinical predictors, and in-hospital outcome of renal replacement therapy (RRT) in acute myocardial infarction (AMI) patients. Methods: All consecutive AMI patients admitted to the Coronary Care Unit between January 1st, 2005 and December 31st, 2015 were identified through a search of our prospectively collected clinical database. Patients were grouped according to whether they required RRT or not. Results: Two-thousand-eight-hundred-thirty-nine AMI patients were included. Eighty-three (3%) AMI patients underwent RRT. Variables confirmed at cross validation analysis to be associated with RRT were: admission creatinine > 1.5 mg/dl (OR 16.9, 95% CI 10.4–27.3), cardiogenic shock (OR 23.0, 95% CI 14.4–36.8), atrial fibrillation (OR 8.6, 95% CI 5.5–13.4), mechanical ventilation (OR 22.6, 95% CI 14.2–36.0), diabetes mellitus (OR 4.8, 95% CI 3.1–7.4), and left ventricular ejection fraction < 40% (OR 9.1, 95% CI 5.6–14.7). The AUC for RRT with the combination of these predictors was 0.96 (95% CI 0.94–0.97; P < 0.001). In-hospital mortality was significantly higher in RRT patients (41% vs. 2.1%, P < 0.001). Oligoanuria as indication for RRT (OR 5.1, 95% CI 1.7–15.4), atrial fibrillation (OR 4.3, 95% CI 1.6–11.5), mechanical ventilation (OR 20.8, 95% CI 6.1–70.4), and cardiogenic shock (OR 12.9, 95% CI 4.4–38.3) independently predicted mortality in RRT-treated patients. The AUC for in-hospital mortality prediction with the combination of these variables was 0.92 (95% CI 0.87–0.98; P < 0.001). Conclusions: Patients with AMI undergoing RRT had strikingly high in-hospital mortality. Use of RRT and its associated mortality were accurately predicted by easily obtainable clinical variables.